2019
DOI: 10.1097/scs.0000000000005462
|View full text |Cite
|
Sign up to set email alerts
|

Definitive Radiation Therapy Versus Postoperative Radiation Therapy for Patients With Maxillary Sinus Cancer Invading the Upper Jaw

Abstract: Maxillectomy following radiation therapy has the strongest local control over maxillary sinus cancer. However, in the advanced stage, complete resection is difficult with adequate margin and has the risk of functional disabilities after surgeries. The objective of the study was to determine the optimal treatment strategy for patients with maxillary sinus cancer invades the upper jaw. A total of 998 histologically confirmed maxillary sinus cancer invades the upper jaw patients were subjected to simple randomiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…1b). Mountains of evidence revealed that comprehensive treatment involving surgery may have a better curative effect than surgery alone [1,[9][10][11]. Similarly, in the present study, 98 patients with MSSCC were divided into four groups: SUR (n = 8), SUR+CT/RT (n = 38), CT/RT+SUR (n = 19), and NON-SUR (n = 33).…”
Section: Therapeutic Outcomes Of Msscc Patientsmentioning
confidence: 53%
See 2 more Smart Citations
“…1b). Mountains of evidence revealed that comprehensive treatment involving surgery may have a better curative effect than surgery alone [1,[9][10][11]. Similarly, in the present study, 98 patients with MSSCC were divided into four groups: SUR (n = 8), SUR+CT/RT (n = 38), CT/RT+SUR (n = 19), and NON-SUR (n = 33).…”
Section: Therapeutic Outcomes Of Msscc Patientsmentioning
confidence: 53%
“…Chemoradiotherapy was confirmed to play an important part in the treatment of MSSCC, especially for tumors with positive margins or high-risk features [20,21]. Mountains of evidence have shown that postoperative chemotherapy and/or radiotherapy are associated with better survival outcomes of MSSCC patients compared with surgery alone [9,16,21]. However, studies that focused on comparisons between upfront surgery and neoadjuvant chemotherapy and/ or radiotherapy followed by surgery in patients with MSSCC showed different results [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, the practitioner should examine for any facial asymmetry or swelling, followed by anterior rhinoscopy to inspect for visible nasal masses, otoscopy to detect dull tympanic membrane, palpation over the neck to reveal neck mass, and completing the examination with a neurological examination to inspect for cranial nerve palsy, I to VI in particular (4) . Maxillary sinus malignancy tends to be associated with oro-nasal, oro-antral fistula, or loose teeth, therefore the involvement of the alveolar process of the maxilla should be ruled out (7) . Nasoendoscopy allows for detailed examination of the nasal cavity anatomy, particularly in cases where the tumour does not completely obstruct the nasal cavity, identification or suggestion of the tumour possible origin, local extension, and anatomy assessment as part of preoperative planning (4) .…”
Section: Discussionmentioning
confidence: 99%
“…In our study stage, margins status and treatment modalities were independent factors not significantly associated with treatment failure. However, in literature, evidence shows that postoperative adjuvant radiotherapy or chemotherapy is associated with better survival outcomes in maxillary sinus malignant tumors than surgery alone [ 32 , 36 , 39 ].…”
Section: Discussionmentioning
confidence: 99%